2015
DOI: 10.5935/0103-507x.20150044
|View full text |Cite
|
Sign up to set email alerts
|

Etiology and prognostic factors of sepsis among children and adolescents admitted to the intensive care unit

Abstract: ObjectiveTo determine the etiology and clinical disease progression variables of sepsis associated with the prognosis of patients admitted to a pediatric intensive care unit.MethodsProspective and retrospective case series. Data were collected from the medical records of patients diagnosed with sepsis who were admitted to the pediatric intensive care unit of a general hospital from January 2011 to December 2013. Bacteria were identified in blood and fluid cultures. Age, sex, vaccination schedule, comorbidities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
2
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 21 publications
(38 reference statements)
2
10
2
3
Order By: Relevance
“…In our study, the etiology of sepsis was identified in 46.7% of cases, similar to other data published in the medical literature [14,15]. In this context, monitoring the kinetics of inflammatory biomarkers in the first 48-72 hours can be a useful method to assess the outcome of patients with sepsis, the response to antimicrobial therapy and the rates of mortality.…”
Section: Discussionsupporting
confidence: 87%
“…In our study, the etiology of sepsis was identified in 46.7% of cases, similar to other data published in the medical literature [14,15]. In this context, monitoring the kinetics of inflammatory biomarkers in the first 48-72 hours can be a useful method to assess the outcome of patients with sepsis, the response to antimicrobial therapy and the rates of mortality.…”
Section: Discussionsupporting
confidence: 87%
“…Dependendo do tipo e da complexidade das CC, muitas crianças precisam de correção cirúrgicas, havendo a necessidade de uma atenção a saúde diferenciada, ainda mesmo durante o pré-natal, uma vez que possa ser diagnosticada precocemente logo nos primeiros meses de vida, aumentando desta forma as chances de sobrevida 12,13 . A predominância de internações em crianças e adolescentes do sexo masculino (60%) vai de encontro com os estudos de Huber et al 14 , diferente de Frota et al 4 , Silva et al 15 e Mourato 16 , que assinalam em seus manuscritos maior índice para o sexo feminino.…”
Section: Discussionunclassified
“…Constatou-se nesse estudo que apenas 19% das crianças e adolescentes internados por cardiopatias tinham Síndrome de Down, enquanto que outros estudos identificaram está síndrome em cerca de 40 a 60%, apontando associação com a cardiopatia congênita e mortalidade nos primeiros anos de vida 2,16 . 21 enfatiza que a escolaridade dos pais é um fator importante, visto que o conhecimento facilita a provisão de cuidados aos seus filhos.…”
Section: Discussionunclassified
“…Mortality in paediatric ICUs is not the same in different countries. It may reach values above 50% and varies across geographical regions: 21% in North America, 29% in Europe, 32% in Australia/New Zealand, 40% in Asia, 11% in South America, and 40% in Africa ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%